Host Liquid Effect on Thermo-Optical Pattern of a Self-Phase Modulated Laser Beam Passing Through Au Nanoparticles Colloids - Hoda Aleali; Ahmad Mehramiz; Elham Valizadeh Pilehroud (Journal of Optoelectronical Nanostructures)
Abstract In this paper, the influence of host liquid’s properties on far-field intensity distribution of a continuous Gaussian laser beam passing through the synthesized colloidal gold nanoparticles (AuNPs) is experimentally and numerically studied considering the different form of heat transfer modes. Our results reveal that dispersed NPs in liquids with more viscosity or less thermal expansion coefficient, lead to more concentric far-field diffraction patterns. By changing the viscosity and thermal expansion coefficient, the form of diffraction patterns due to the convection effect, can dramatically change compared to the strength of the thermal nonlinear refraction. The effect of the linear absorption coefficient of the medium on diffraction patterns of the colloids is also investigated. It is shown that by increasing the linear absorption coefficient of the medium, the number of the rings and the beam divergence increase under exposure of the 532 nm laser beam. Our observations show the excellent sensitivity of the diffraction ring pattern technique to characterize the different modes of heat transfer and thermo-optical nonlinear properties of the NPs colloids.